Metal Free Reversible-Deactivation Radical Polymerizations: Advances, Challenges, and Opportunities - Kreutzer, Johannes (Polymers (Basel), 2017)
A considerable amount of the worldwide industrial production of synthetic polymers is currently based on radical polymerization methods. The steadily increasing demand on high performance plastics and tailored polymers which serve specialized applications is driven by the development of new techniques to enable control of polymerization reactions on a molecular level. Contrary to conventional radical polymerization, reversible-deactivation radical polymerization (RDRP) techniques provide the possibility to prepare polymers with well-defined structures and functionalities. The review provides a comprehensive summary over the development of the three most important RDRP methods, which are nitroxide mediated radical polymerization, atom transfer radical polymerization and reversible addition fragmentation chain transfer polymerization. The focus thereby is set on the newest developments in transition metal free systems, which allow using these techniques for biological or biomedical applications. After each section selected examples from materials synthesis and application to biomedical materials are summarized.